2014
DOI: 10.3892/or.2014.3193
|View full text |Cite
|
Sign up to set email alerts
|

Global fecal microRNA profiling in the identification of biomarkers for colorectal cancer screening among Asians

Abstract: Fecal microRNAs (miRNAs) are increasingly explored as non-invasive markers of colorectal cancer (CRC). However, its holistic profile in Asian CRC patients remains elusive. In the present study, the global human fecal miRNAs in Asian Chinese CRC patients was assayed to elucidate novel diagnostic fecal markers. Additionally, the influence of blood in stool on fecal miRNA levels was investigated for the first time. Microarray analysis was applied to profile the fecal miRNAs extracted from CRC patients and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…The combination of cytology and the miRNA signature had a positive predictive value > 99% (76). MiRNA biomarker discovery studies have also been performed using fecal samples for the screening of colon cancer (77, 78) and pancreatic cancer (79). Together, these studies show that the use of protein and/or miRNA panels can improve the predictive values of the current procedures and out-perform the use of a single biomarker for classifying disease types, giving a prognosis or diagnosis, and predicting the therapeutic response.…”
Section: Ii- Biomarker Signaturesmentioning
confidence: 99%
“…The combination of cytology and the miRNA signature had a positive predictive value > 99% (76). MiRNA biomarker discovery studies have also been performed using fecal samples for the screening of colon cancer (77, 78) and pancreatic cancer (79). Together, these studies show that the use of protein and/or miRNA panels can improve the predictive values of the current procedures and out-perform the use of a single biomarker for classifying disease types, giving a prognosis or diagnosis, and predicting the therapeutic response.…”
Section: Ii- Biomarker Signaturesmentioning
confidence: 99%
“…4, 5 Many miRNAs were found to be aberrantly expressed in colorectal cancer (CRC) with the downregulation of miR-601, miR-192, miR-345, miR-215, and miR-612, and the upregulation of miR-223, miR-18a, miR-155, miR-31, and miR-224, when compared with those found in normal colon mucosa. 6, 7, 8, 9 Given their involvement in the initiation, progression, and metastasis of human cancers, some of these miRNAs have become studies of great interest. For example, it has been shown that levels of miR-143 and miR-145 tend to be lower in CRC tissue than in normal tissue.…”
mentioning
confidence: 99%
“…MiR-223 Fig. 4 Forest plots of multivariable meta-regression analyses for sensitivity and specificity and miR-451, measured in the feces samples, appear to have an aberrant expression profile between the CRC patients and healthy people [39]. The significant difference of expression level was also discovered in miR-21, let-7g, miR-31, miR-92a, miR-181b, and miR-203.…”
Section: Discussionmentioning
confidence: 95%
“…After the full-texts review, another 43 studies were excluded, including 14 studies irrelevant to diagnosis, 19 studies without sufficient data, 5 studies about metastatic disease, and other 5 studies with duplicate data. Finally, 29 eligible articles were included in our metaanalysis, including 19 articles about blood-based miRNAs assays [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and 10 articles about feces-based miRNAs assays [3,5,[32][33][34][35][36][37][38][39].…”
Section: Literature Searchmentioning
confidence: 99%